PROFIL DAN PERMASALAHAN SISTEM LOGISTIK SUNGAI DI KABUPATEN KUBU RAYA PROVINSI KALIMANTAN BARAT - AKBAR, MUHAMMAD FIKRI (Jurnal TIN Universitas Tanjungpura, 2017)
West Kalimantan is one area that is often dubbed as the "Thousand Rivers Region" because of West Kalimantan are fed by hundreds of rivers and small which are still frequent and are navigable. Most of the major rivers is still often used as a means of transport path, both people and goods. One of the areas / districts in the province of West Kalimantan still take the river route to transport activity (people / goods) is Kubu Raya. In essence the river path through every district in Kubu Raya has a very important role in the activity of logistics activities, both the distribution as well as loading and unloading activities. Given the importance of the activity of the logistics activities through the river, but the resources that explain the logistics system of the river in Kubu Raya which is currently still in existence. In addition, research conducted on the logistics system of the river is still very rare. This research aims to obtain data and information on the profile and problems of logistics river system. This research is a case study (case study) that is descriptive qualitative survey method and observation. In addition, the literature that comes from a book published by BPS (Central Bureau of Statistics) and data BAPPEDA (Regional Development Planning Board) is also a method used to complete the data and information required in this study. Limitation of the study area in this study include the District of Kuala Mandor B, Kubu, Terentang, Teluk Pakedai, Batu Ampar and Rasau Jaya. The results of this study explain that in general transport activity in Kubu Raya is done through access to the river path. Transport activity performed using several types of transport stream that has its own functions and mechanisms. When present, the activity of the transport through the river has experienced a shift that tends to land transportation. Logistics system problems affecting the river due to road infrastructure became available, the start of the siltation of rivers, less terawatnya existing river channels, insufficient logistics facilities and construction of the bridge (bullying) is not well organized. Although the transport activity through the river has undergone a shift, but still there is one district that most of the activity was carried out through the river, namely the Kubu district. Based on the analysis using the logistic mechanism SocNetV- 2.1 applications to determine the logistics center of the six districts under study on the city of Pontianak, found that the exact location serve as the central logisitk located in Kubu district, precisely in the village of Kubu.Keywords : geographical conditons, inland waterway,                   logistics system